Asuhan Keperawatan Anak Pada Pasien Dengan Gastroenteritis Akut (GEA) Di Ruangan Anak RSUD PROF. H. Muhammad Yamin S.H Pariaman - Ninda Dwi agustin; Reska Handayani; Prima Yoselina; Erpita Yanti (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Acute gastroenteritis (AGE) is an inflammation of the gastrointestinal tract characterized by diarrhea and vomiting, which can lead to dehydration. Based on data from the pediatric ward of RSUD Prof. H. M. Yamin, S.H. Pariaman, AGE is among the top ten most common diseases and ranked second in 2025 with a total of 130 cases. This condition indicates that AGE remains a health problem requiring optimal management through comprehensive nursing care. This study aimed to provide direct nursing care to a patient diagnosed with acute gastroenteritis through the stages of assessment, nursing diagnosis, intervention, implementation, and evaluation. This study used a case study approach conducted from February 11 to 15, 2026, in the pediatric ward of RSUD Prof. H. M. Yamin, S.H. Pariaman, with An. H as the subject. The assessment results identified four nursing diagnoses: hypovolemia related to fluid loss, diarrhea related to increased intestinal peristalsis, impaired skin integrity related to irritation, and risk of infection related to microorganism exposure, with hypovolemia as the priority diagnosis. After five days of nursing care, the patient’s condition improved, as indicated by adequate fluid balance, decreased frequency of diarrhea, improved skin condition, and no signs of infection. In conclusion, comprehensive and continuous nursing care plays an important role in accelerating the recovery of patients with acute gastroenteritis. It is recommended that healthcare providers enhance fluid monitoring and provide education to families regarding adequate fluid intake, food hygiene, and the importance of seeking healthcare services promptly if the patient’s condition worsens.